(untitled) (Nigerian Journal of Physiological Sciences, 2024)
Status epilepticus, histology, and neurobehavioral parameters of pentylenetetrazole-induced epileptic wistar rats were being investigated following administration of Musa paradisiaca (MP) stem juice. A seizure was induced sixty minutes after the administration of graded doses of Musa paradisiaca stem juice and diazepam, an anticonvulsant drug. A neurobehavioral test was carried out after pentylenetetrazole (PTZ) induction. The animals were arbitrarily given five groups, namely: A, B, C, D, and E. Group A animals functioned as the normal control, given rat pellets and distilled water. Group B served as the PTZ control, and the animals were administered 65mg/kg body weight of PTZ intraperitoneally. Group C served as the PTZ + Diazepam (DZP) treated group, and the animals were administered orally 4 mg/kg body weight of diazepam 60 minutes before administration of PTZ intraperitoneally. Group D and E served as the PTZ + MP [Low dose and High dose] pre-treated groups, given 2500 mg/kg and 5000 mg/kg body weight of MP stem juice, respectively, for 7 days orally before administration of PTZ intraperitoneally and 1 hour post treatment with MP stem juice. Significant antiepileptic effects on status epilepticus were observed in MP stem juice (2500mg/kg and 5000mg/kg) and the Diazepam group of animals. These antiepileptic effects were clearly seen in the delay recorded in latency of seizure and latency of tonic-clonic seizure, a reduced frequency of myoclonic jerks and a 100% mortality index rate recorded in the MP stem juice pre-treated animals. Histological sections of the hippocampus pre-treated with Musa paradisiaca stem juice and diazepam revealed significant differences in the structural integrity when compared with the epileptic control. The novel object recognition task test carried out showed a positive score for long-term memory as attained by animals in Group D and E when compared to Group B animals that had a negative score for long-term memory. In this study, the administration of Musa paradisiaca stem juice limited the extent of status epilepticus, reduced cytoarchitectural damage caused by epilepsy, and further enhanced long-term recognition memory in the MP stem juice pre-treated epileptic rats.